2020
DOI: 10.1177/1934578x20918687
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Improves Glycemic Control, Insulin Sensitivity, and Oxidative Stress in Hyperglycemic Subjects: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: The aim of this research was to investigate the effects of nutraceuticals including bitter melon, fenugreek, cinnamon, alpha-lipoic acid, zinc, biotin, chromium, and cholecalciferol on glycemic control, insulin sensitivity, lipid profiles, oxidative stress, and inflammatory markers in hyperglycemia. The study design was a randomized, double-blind, placebo-controlled trial. Subjects with hyperglycemia were randomly divided into 2 groups. The treatment group ( n = 52) was given a nutraceutical and the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Acerola and Gotukola, integral to Nutrilite ® Daily Plus formulation, further contribute to this effect by influencing the AKT AMPK pathway, resulting in an increased antioxidant status. Moreover, Gotukola's enhancement of the NRF anti-inflammatory pathway leads to a substantial 79% reduction in inflammation, surpassing the 18% reduction reported in the study by Bumrungpert et al 56 .…”
Section: Discussionmentioning
confidence: 56%
“…Acerola and Gotukola, integral to Nutrilite ® Daily Plus formulation, further contribute to this effect by influencing the AKT AMPK pathway, resulting in an increased antioxidant status. Moreover, Gotukola's enhancement of the NRF anti-inflammatory pathway leads to a substantial 79% reduction in inflammation, surpassing the 18% reduction reported in the study by Bumrungpert et al 56 .…”
Section: Discussionmentioning
confidence: 56%
“…A study by Shekarchizadeh-Esfahani et al concluded that administering cinnamon at daily dosages of <1,500 mg for at least 12 weeks significantly reduced ALT levels ( p = 0.002) ( 79 ). Although cinnamon’s effect on liver function remains unclear, several studies reported cinnamon’s interaction with peroxisome proliferator-activated receptor (PPAR) which ultimately improves insulin resistance, down-regulates pro-inflammatory cytokine levels, and decreases serum AST levels ( 79 , 80 ). Longe et al also looked at the hepatoprotective properties of cinnamon on alloxan induced diabetic rats ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived dietary supplements and nutraceuticals are becoming increasingly popular all over the world as a result of growing customer awareness regarding their potential health benefits [35]. It is well established that some plant polyphenols like flavonoids have beneficial effects on general cardiometabolic health and may modulate the risk of the development of cardiovascular and metabolic diseases, including diabetes and its vascular complications [36,37]. The literature provides studies on the phytochemical composition of Citrus sinensis and Punica granatum and confirms that both plants are abundant in bioactive polyphenolic components, mainly flavonoids in the case of sweet orange and ellagitannins in the case of pomegranate fruit [38,39].…”
Section: Introductionmentioning
confidence: 99%